A novel pressed porous silicon-polycaprolactone composite as a dual-purpose implant for the delivery of cells and drugs to the eye. (October 2015) - Irani, Yazad D.; Tian, Yuan; Wang, Mengjia; Klebe, Sonja; McInnes, Steven J.; Voelcker, Nicolas H.; Coffer, Jeffery L.; Williams, Keryn A.
Abstract: Dysfunction of corneal epithelial stem cells can result in painful and blinding disease of the ocular surface. In such cases, treatment may involve transfer of growth factor and normal adult stem cells to the ocular surface. Our purpose was to develop an implantable scaffold for the delivery of drugs and cells to the ocular surface. We examined the potential of novel composite biomaterials fabricated from electrospun polycaprolactone (PCL) fibres into which nanostructured porous silicon (pSi) microparticles of varying sizes (150–250 μm or <40 μm) had been pressed. The PCL fabric provided a flexible support for mammalian cells, whereas the embedded pSi provided a substantial surface area for efficient delivery of adsorbed drugs and growth factors. Measurements of tensile strength of these composites revealed that the pSi did not strongly influence the mechanical properties of the polymer microfiber component for the Si loadings evaluated. Human lens epithelial cells (SRA01/04) attached to the composite materials, and exhibited enhanced attachment and growth when the materials were coated with foetal bovine serum. To examine the ability of the materials to deliver a small-drug payload, pSi microparticles were loaded with fluorescein diacetate prior to cell attachment. After 6 hours (h), cells exhibited intracellular fluorescence, indicative of transfer of the fluorescein diacetate into viable cells and its subsequent enzymatic conversion to fluorescein. To investigate loading of large-molecule biologics, murine BALB/c 3T3 cells, responsive to epidermal growth factor, insulin and transferrin, were seeded on composite materials. The cells showed significantly more proliferation at 48 h when seeded on composites loaded with these biologics, than on unloaded composites. No cell proliferation was observed on PCL alone, indicating the biologics had loaded into the pSi microparticles. Drug release, measured by ELISA for insulin, indicated a burst followed by a slower, continuous release over six days. When implanted under the rat conjunctiva, the most promising composite material did not cause significant neovascularization but did elicit a macrophage and mild foreign body response. These novel pressed pSi–PCL materials have potential for delivery of both small and large drugs that can be released in active form, and can support the growth of mammalian cells. Highlights: We fabricated novel pressed porous silicon-polycapralactone composite materials. The materials supported the attachment and growth of mammalian cells. Small molecule drugs and biologics were loaded into the composites. The materials elicited a weak foreign body response under the rat conjunctiva. Composite materials may be of use for the transfer of cells and drugs to the ocular surface.